2016
DOI: 10.18632/oncotarget.11628
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor-1 mediates the expression of the immune checkpoint HLA-G in glioma cells through hypoxia response element located in exon 2

Abstract: HLA-G is an immune checkpoint molecule with specific relevance in cancer immunotherapy. It was first identified in cytotrophoblasts, protecting the fetus from maternal rejection. HLA-G tissue expression is very restricted but induced in numerous malignant tumors such as glioblastoma, contributing to their immune escape. Hypoxia occurs during placenta and tumor development and was shown to activate HLA-G. We aimed to elucidate the mechanisms of HLA-G activation under conditions combining hypoxia-mimicking treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 105 publications
(108 reference statements)
4
64
0
Order By: Relevance
“…Moreover and surprisingly, UTR1, which is theoretically associated with higher HLA-G expression, exists in the HLA-G- cell line (HLA-G mRNA relative to JEG-3: ~1.10 −4 ) exclusively, whilst UTR-2 and UTR-4, which are theoretically associated with intermediate HLA-G expression, occur in M8 and U251MG, respectively. We have previously showed that the M8 HLA-G promoter is strongly methylated [36] and that demethylation treatment upregulates HLA-G transcription in M8 [16, 36] and U251MG cells [37, 49]. This result first suggests that the HLA-G gene is functional in these cell lines especially because U251MG-treated cells may produce HLA-G protein [37, 49].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover and surprisingly, UTR1, which is theoretically associated with higher HLA-G expression, exists in the HLA-G- cell line (HLA-G mRNA relative to JEG-3: ~1.10 −4 ) exclusively, whilst UTR-2 and UTR-4, which are theoretically associated with intermediate HLA-G expression, occur in M8 and U251MG, respectively. We have previously showed that the M8 HLA-G promoter is strongly methylated [36] and that demethylation treatment upregulates HLA-G transcription in M8 [16, 36] and U251MG cells [37, 49]. This result first suggests that the HLA-G gene is functional in these cell lines especially because U251MG-treated cells may produce HLA-G protein [37, 49].…”
Section: Discussionmentioning
confidence: 94%
“…We have previously showed that the M8 HLA-G promoter is strongly methylated [36] and that demethylation treatment upregulates HLA-G transcription in M8 [16, 36] and U251MG cells [37, 49]. This result first suggests that the HLA-G gene is functional in these cell lines especially because U251MG-treated cells may produce HLA-G protein [37, 49]. Second, in the present work we have tested the impact of HLA-G 3’UTR polymorphism irrespective of modifications in chromatin, and we have focused on post-transcriptional mechanisms only.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the impact of hypoxic stress in HLA-G expression in U251MG glioblastoma cell line was explored [32]. In this study, under hypoxia, the U251MG cells (HLA-G − ) induced significant HLA-G transcriptional activity compared to untreated cells, but with negative protein detection.…”
Section: Hla-g Expression In Hypoxic Stress Conditionsmentioning
confidence: 93%
“…The authors found by in silico analysis, a new HIF-1 binding site located in the HLA-G coding sequence at exon 2, 281 base pairs after start nucleotide [32]. This novel +281 HRE comprehends two hypoxia binding sites (HBS), one at +281 bp (sense, 5′-ACGTG-3′) and one at +291 bp (antisense, 5′-CACGC-3′) positions [32].…”
Section: Evidences Of Hla-g Balanced Expression Through Hif-1 In Tmentioning
confidence: 99%
“…Two mechanisms that involve HIF activity and provide immune privilege in the placenta are immune invisibility (where fetal cells are invisible to the mother’s immune system) and immune blockade (where the mother’s immune system is blocked in the placenta). The placenta avoids immune attack mostly through trophoblast expression of the non-classical class I histocompatibility antigen HLA-G, a HIF1α-dependent gene product that protects against attack by natural killer cells 95,96 . Immune blockade in the placenta is provided by hypoxia-dependent regulation of factors such as programmed cell death 1 ligand 1 (PDL1), which inactivates or induces cell death in infiltrating T cells 95 .…”
Section: Hypoxia In Physiological Immune Nichesmentioning
confidence: 99%